2021
DOI: 10.3390/agronomy11050897
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Transcriptome Analysis of Potato with Differential Tolerance to Bentazone Herbicide

Abstract: Potato (Solanum tuberosum), an important food crop worldwide, is threatened by broadleaf weeds. Bentazone is an effective herbicide for controlling weeds; however, as a photosynthesis inhibitor, it can also affect potato plants. Therefore, screening potato seedlings for bentazone resistance and determining the genes involved is essential. Herein, we selected potato varieties with tolerance and sensitivity to bentazone. The photosynthetic rate of sensitive plants was notably affected by bentazone application, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…We found that BNTZ exposure reduced the chlorophyll content in rice leaves, which was associated with impaired photosynthesis in rice and reduced production of plant energy and materials. Our result is consistent with the previous report on potato under BNTZ treatment . This result was also reinforced by the chlorophyll fluorescence parameters.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that BNTZ exposure reduced the chlorophyll content in rice leaves, which was associated with impaired photosynthesis in rice and reduced production of plant energy and materials. Our result is consistent with the previous report on potato under BNTZ treatment . This result was also reinforced by the chlorophyll fluorescence parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Our result is consistent with the previous report on potato under BNTZ treatment. 31 This result was also reinforced by the chlorophyll fluorescence parameters. The maximum photochemical efficiency (Fv/Fm) of PSII significantly decreased under BNTZ stress, indicating that the PSII reaction centers was impaired.…”
Section: ■ Discussionmentioning
confidence: 75%
“…Bentazone [3-Isopropyl-1H-2,1,3-benzothiadiazin-4(3H)-one 2,2-dioxide] was first documented in 1975. Bentazone is a POST herbicide used to control broadleaf weeds in the cultivation of cereals, legumes [6], vegetables [17], and tuber crops [18]. Bentazone is a contact herbicide that inhibits the capacity of vulnerable plants to use sunlight in photosynthesis to produce the energy necessary for survival.…”
Section: Introductionmentioning
confidence: 99%
“…Weed control strategies in crop production can be divided into chemical and nonchemical practices (Zangoueinejad and Kazemeini, 2014;Azadbakht et al, 2017;Zangoueinejad et al, 2018;Zangoueinejad, 2019;El-Metwally and El-Wakeel, 2019;Nabati Souha et al, 2020a,b;Zangoueinejad et al, 2021). Although various herbicide options are available to control weed abundances in crop fields worldwide (Alebrahim et al, 2011;Khatami Kalkhoran et al, 2017;Zangoueinej ad et al, 2019;Alebrahim et al, 2021;Guo et al, 2021). However, cover crops can be considered an effective weed control strategy in sustainable agriculture by reducing the side effects of herbicide use, improving soil quality over time and increasing crop yield production (Barbas et al, 2020).Therefore, due to the destructive effects of herbicides on natural resources, concerns have been raised in recent years (Zangoueinejad andGhadiri 2014, 2016;Mehdizadeh et al, 2017;Alebrahim et al, 2017;Hashemi et al, 2021;Camargo et al, 2020;Zangoueinejad and Alebrahim, 2021b) leading to an increased attention on their negative effects on the ecosystems, including soil and water pollution and its phytotoxic effects on crops in rotation (Mehdizadeh, 2016;Azadbakht et al, 2019;Khatami Kalkhoran et al, 2017;Zangoueinejad and Alebrahim, 2021a).…”
Section: Introductionmentioning
confidence: 99%